Circulating H5N1 virus among native chicken living around commercial layer farms - Tarigan, Simson; Indriani, Risa; Ignjatovic, J. (Indonesian Journal of Animal and Veterinary Sciences, 2015)
Soon after the application of vaccination programme against high pathogenic avian influenza H5N1 outbreak of the disease in breeder and commercial layer farms has diminished remarkably in West Java. This study aimed to investigate whether the H5N1 decline is related to the disappearance of source of infection around the farms. Serum samples were collected from 421 native chicken living around commercial layer farms in the Districs of Cianajur and Sukabumi, West Java in March-April 2014.Â  Antibodies to avian influenza virus (AIV) H5N1 were measured using haemaglutination inhibition (HI), ELISAs and immunoblotting that measured presence of antibodies to the haemagglutin of H5N1 strain, as well as the M2e and nucleoprotein (NP) of all avian influenza viruses. Based on the combined results, 8.6% of the native chickens were seropositive to AI virus based on one or more of serological tests. This study provided serological evidence that H5N1 virus was still circulating among native chicken living around commercial layer farms. Many positive sera were however positive for antibodies in one test only: 2.4%, 3.3% and 3.8% by HI test, M2e and NP ELISA, respectively. It could be speculated that the incongruity of the results is due to the fact that HI, MM2e ELISA and NP ELISA all measure different type of antibodies and the duration of these antibodies in serum following infection with H5N1 differ. The fact that H5N1 virus is still circulating around commercial layer farms infers that the commercial farms are still under threat and therefore vaccination and strict biosecurity are still needed. Key Words: H5N1, Native Chicken, Commercial Layer, Nucleoprotein, M2e, HI Test